\(\frac{4}{6}+\frac{7}{13}+\frac{17}{9}+\frac{19}{13}+\frac{1}{9}+\frac{14}{6}\)
\(=\left(\frac{4}{6}+\frac{14}{6}\right)+\left(\frac{7}{13}+\frac{19}{13}\right)+\left(\frac{17}{9}+\frac{1}{9}\right)\)
\(=3+2+2=7\)
4/6 + 7/13 + 17/9 + 19/13 + 1/9 + 14/6. = ( 4/6 + 14/6 ) + ( 7/13 + 19/13 ) + ( 17/9 + 1/9 ). = 18/6 + 26/13 + 18/9. = 3 + 2 + 2 = 7.
\(\frac{4}{6}+\frac{7}{13}+\frac{17}{9}+\frac{19}{13}+\frac{1}{9}+\frac{14}{6}=\left(\frac{4}{6}+\frac{14}{6}\right)+\left(\frac{7}{13}+\frac{19}{13}\right)\)\(+\left(\frac{17}{9}+\frac{1}{9}\right)=\frac{18}{6}+\frac{26}{13}+\frac{18}{9}=3+2+2=7\)
Bài làm :
Ta có :
\(\frac{4}{6}+\frac{7}{13}+\frac{17}{9}+\frac{19}{13}+\frac{1}{9}+\frac{14}{6}\)
\(=\left(\frac{4}{6}+\frac{14}{6}\right)+\left(\frac{7}{13}+\frac{19}{13}\right)+\left(\frac{17}{9}+\frac{1}{9}\right)\)
\(=\frac{18}{6}+\frac{26}{13}+\frac{18}{9}\)
\(=3+2+2\)
\(=7\)
\(\frac{4}{6}+\frac{7}{13}+\frac{17}{9}+\frac{19}{13}+\frac{1}{9}+\frac{14}{6}=\left(\frac{4}{6}+\frac{14}{6}\right)+\left(\frac{7}{13}+\frac{19}{13}\right)+\left(\frac{17}{9}+\frac{1}{9}\right)\)
\(=2+2+3=7\)
\(\frac{4}{6}+\frac{7}{13}+\frac{17}{9}+\frac{19}{13}+\frac{1}{9}+\frac{14}{6}\)
\(=\left(\frac{4}{6}+\frac{14}{6}\right)+\left(\frac{7}{13}+\frac{19}{13}\right)+\left(\frac{17}{9}+\frac{1}{9}\right)\)
\(=\frac{18}{6}+\frac{26}{13}+\frac{18}{9}\)
\(=3+2+2\)
\(=7\)